Neuropsychological Predictors of Trauma Centrality in OIF/OEF Veterans - Hart, Roland P.; Bagrodia, Rohini; Rahman, Nadia; Bryant, Richard A.; Titcombe-Parekh, Roseann; Marmar, Charles R.; Brown, Adam D. (Frontiers in Psychology, 2017)
This study examined whether reduced performance on two neuropsychological tasks, cognitive flexibility and working memory, were associated with higher levels of trauma centrality. A growing body of research has shown that trauma centrality, the extent to which a person believes a potentially traumatic event has become central to their self-identity and life story, is associated with Posttraumatic Stress Disorder (PTSD). Furthermore, PTSD is often associated with alterations in neuropsychological functioning. The relationship between neuropsychological processes and trauma centrality, however, has yet to be explored. OEF/OIF combat veterans (N=41) completed the Posttraumatic Diagnostic Scale (PDS), the Beck Depression Inventory-II (BDI-II), the Centrality of Event Scale (CES), and on-line measures of cognitive flexibility and working memory assessed via WebNeuro. Bivariate Pearson correlations showed that CES scores were positively correlated with PDS and BDI scores, and negatively correlated with cognitive flexibility and working memory. Linear regressions revealed that working memory significantly predicted CES when controlling for depression and PTSD severity while cognitive flexibility approached significance when controlling for these same variables. This study employed a cross-sectional design, precluding causality. The small sample size, entirely male sample, and use of an online neuropsychological assessment warrant follow-up research. Although numerous studies have found an association between CES and PTSD, this is the first to suggest that neuropsychological processes underlie the construct of trauma centrality. Given the importance of maladaptive cognitive processes underlying the pathogenesis of PTSD, these data suggest that future studies aimed at examining the link between neuropsychological processes and maladaptive cognitive processes, such as trauma centrality, may help characterize and treat PTSD.